Toulouse face à la Garonne: emprise de l'urbanisation dans la plaine inondable et geohistoire des amenagements fluviaux - Valette, Philippe; Carozza, Jean Michel (Geographicalia, 2014)
The city of Toulouse in France settled on the banks of the Garonne. The evolution of the urbanization of the city reflects the ambivalent relationship with the river: scourge to fight against dams which is landscape, but also sought to resource which is created mills, ports ... The historical geography of river developments facing urbanization reveals the development and juxtaposition of artifacts on the river. Urban river landscapes Toulouse are the result of a slow time construction. The objective of this work is to define these different temporalities that produced the current river landscapes. These are the subject of development projects and their implementation will change the looks by putting the Garonne in the center and heart of the city.
Keywords: Toulouse; Garonne; urbanization; river engineering; resource; flood; geo-history; report city / river; temporality; river landscapes.